PENGELOLAAN PENDAPATAN ASLI DESA DARI TANAH KAS DESA OLEH PEMERINTAH DESA (Studi di Desa Sungai Seria Kecamatan Ketunggau Hulu Kabupaten Sintang) - Redin Redin (Universitas Kapuas Sintang, 2022)
Village Original Income (PADes) for Sungai Seria Village is obtained from village assets. Village assets owned by the Sungai Seria Village Government are in the form of Village Treasury Land handed over by the Village Government to PT. Dhanista Surya Nusantara for oil palm plantations. On this land, the village government through village regulations no. 1 of 2020 concerning Management of Sungai Village Cash Land, stipulates a rental price for 200 hectares of land, resulting in PADes since 2020. Management of village assets is an important concern for the village government, because good management of village assets has an impact on increasing PADes. This study aims to find out how the Village Original Income is managed which is sourced from the results of village treasury land rental fees by the Sungai Seria Village Government. This study uses an empirical juridical approach, with descriptive data analysis, to determine the sample used purposive sampling technique. Data collection techniques through interviews, observation and documentation.The results showed that the Sungai Seria Village Government was able to take advantage of village assets in the form of village assets, namely village treasury land that had been handedover by the Village Government together with the community to be turned into oil palm plantations by PT. Dhanista Surya Nusantara. For this land, the village government sets a rental price, the payment of which is from the remaining results of the company’s operations through the Aboh Kitai oil palm smallholders cooperative from 2020 until now. The management of PADes from the rental price of the village treasury land has been carried out by the village government based on Minister of Home Affairs Regulation Number 20 of 2018 and Sintang Regent Regulation Number 22 of 2017, but the management has not been entirely to optimize the development and development of village communities.